The ORF8 Protein of SARS-CoV-2 Modulates the Spike Protein and Its Implications in Viral Transmission - Chou, Jen-Mei; Tsai, Jo-Ling; Hung, Jo-Ning; Chen, I-Hua; Chen, Szu-Ting; Tsai, Ming-Han (Frontiers in Microbiology, 2022)
COVID-19 is currently global pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Accompanying the rapid spread of the error-prone RNA-based genome, several dominant SARS-CoV-2 variants have been genetically identified. The mutations in the spike protein, which are essential for receptor binding and fusion, have been intensively investigated for their contributions to viral transmission. Nevertheless, the importance of other viral proteins and their mutations in SARS-CoV-2 lifecycle and transmission remains fairly understood. Here, we report the strong potency of an accessory protein ORF8 in modulating the level and processing of the spike protein. The expression of ORF8 protein does not affect propagation but expression of spike protein, which may lead to pseudovirions with less spike protein on the surface, therefore less infection potential. At the protein level, ORF8 expression led to downregulation and insufficient S1/S2 cleavage of the spike protein in a dose-dependent manner. ORF8 exhibits a strong interaction with the spike protein mainly at S1 domains and mediates its degradation through multiple pathways. The dominant clinical isolated-ORF8 variants with the reduced protein stability, exhibited the increased capacity of viral transmission without compromising their inhibitory effects on HLA-A2. Although the increase in spike proteins level and spike-pseudovirus production observed by using highly transmissible clinical spike variants, there was no significant compromise in ORF8-mediated downregulation. Because ORF8 is important for immune surveillance and might be required for viral fitness in vivo, the alteration of the spike protein might be an optional strategy used by SARS-CoV-2 to promote viral transmission by escaping the inhibitory effects of ORF8. Therefore, our report emphasized the importance of ORF8 in SARS-CoV-2 spike protein production, maturation, and possible evolution.